Top Incomes, Rising Inequality, and Welfare - Kevin J. Lansing; Agnieszka Markiewicz (Center for Economic Studies and ifo Institute (CESifo), 2015)
We introduce permanently-shifting income shares into a standard growth model with two types of agents. Capital owners represent the top quintile of U.S. households while workers represent the remainder. Our tractable model allows us to exactly replicate the observed U.S. time paths of the top quintile income share, capital's share of income, and key macroeconomic variables over the period 1970 to 2013. For the baseline simulation, the welfare gain for capital owners is 3.7% of per-period consumption while workers suffer a welfare loss of 1.4%. Using counterfactual simulations, we find that both groups could have achieved gains if redistributive government transfers had increased to around 18% of total output by the year 2013 - somewhat higher than the actual value of around 15% observed in the data.
Keywords: D31; E32; E44; H21; O33; 330; top incomes; inequality; distribution shocks; redistributive transfer payments; welfare